2017
DOI: 10.1111/jne.12540
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal overfeeding by small‐litter rearing sensitises hippocampal microglial responses to immune challenge: Reversal with neonatal repeated injections of saline or minocycline

Abstract: The early-life period is extremely vulnerable to programming effects from the environment, many of which persist into adulthood. We have previously demonstrated that adult rats overfed as neonates have hypothalamic microglia that are hyper-responsive to an immune challenge, as well as hippocampal microglia that respond less efficiently to learning. We therefore hypothesised that neonatal overfeeding would alter the ability of hippocampal microglia to respond to an immune challenge with lipopolysaccharide (LPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 86 publications
(197 reference statements)
2
15
1
Order By: Relevance
“…On the other hand, overfeeding during lactation cause a positive response in the hippocampus antioxidant enzymes activities, evidenced by an increase in SOD, GPx, and GLO 1. We thought that this occurs in response to the pro‐inflammatory environment found in this structure in the litter size reduction model as a possible explanation to the antioxidant network improvement (De Luca et al, 2017, 2016). Despite on adult mice exposed to overfeeding during lactation decreased spatial memory was already demonstrated (Salari et al, 2018), at weaning we did not found oxidative stress markers elevated.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, overfeeding during lactation cause a positive response in the hippocampus antioxidant enzymes activities, evidenced by an increase in SOD, GPx, and GLO 1. We thought that this occurs in response to the pro‐inflammatory environment found in this structure in the litter size reduction model as a possible explanation to the antioxidant network improvement (De Luca et al, 2017, 2016). Despite on adult mice exposed to overfeeding during lactation decreased spatial memory was already demonstrated (Salari et al, 2018), at weaning we did not found oxidative stress markers elevated.…”
Section: Discussionmentioning
confidence: 89%
“…In our previous work, we demonstrated that neonatal overfeeding increases microglial numbers in the adult PVN, as well as Il‐6 gene expression in the hypothalamus and Tlr4 expression in the hippocampus, relative to normally fed controls. LPS further increases PVN, ARC and hippocampal microglial numbers in the neonatally overfed after 24 hours. In the present study, we examined whether this effect of neonatal overfeeding on central inflammatory profiles after LPS could be attenuated with minocycline.…”
Section: Resultsmentioning
confidence: 90%
“…Both low and high dose treatments robustly reduced the increase in activated microglia. We used these findings as guidance for our own selection of minocycline dose in this and our previous study . For these experiments, we used n = 6 per group, with the members of each group being derived from at least four litters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early-life period has been increasingly studied as the most optimal time to intervene in this epidemic. It is suggested that the early life period is particularly susceptible to environmental "programming" effects that have been evidenced to remain present much later in life [2,3]. Specifically, rapid weight gain early in life due to improper feeding practices has been shown to be a risk factor for obesity later in childhood [3,4].…”
Section: Introductionmentioning
confidence: 99%